PENGARUH PENDAPATAN, BIAYA BUNGA, BIAYA OPERASIONAL, DAN ARUS KAS OPERASI TERHADAP LABA BERSIH PERUSAHAAN JASA KEUANGAN DI BEI TAHUN 2020-2024 - Rizki Octa Arum Sartika; Suhesti Ningsih; Hadi Samanto (CV. Denasya Smart Publisher, 2025)
This research aims to analyze the influence of income, interest expenses, operational costs, and operating cash flow on the net profit of service companies in the financial sector listed on the Indonesia Stock Exchange (IDX) during the period of 2020–2024. This research is a type of descriptive study with a quantitative approach. The population in this study consists of 105 service companies in the financial sector, with the sampling technique using purposive sampling method, resulting in 30 companies as the sample. The data source used is secondary data obtained from the official website of the Indonesian Stock Exchange (IDX). The data analysis methods used include descriptive statistical tests, classical assumption tests, as well as hypothesis testing consisting of F tests, t tests, multiple linear regression analysis, and the coefficient of determination (R²) test. Research results indicate that partially the variables of income, interest costs, operating costs, and operating cash flow have a significant effect on the company’s net profit.